sWOM and Online Shopping within a Disease Menace: The Case of Vietnam - Le, Xuan Cu; Chu, Ba Quyet (Organizations and Markets in Emerging Economies, 2022)
Although electronic word-of-mouth via social networking sites (or sWOM) greatly induced online shopping, its importance in shopping decisions during the coronavirus disease (COVID-19) pandemic has not been holistically considered. Based on the necessity of sWOM, uses and gratifications theory (UGT), and health belief theory (HBT), this study frames a consumer shopping tendency model toward sWOM in the context of the pandemic. A web-based survey was designed to collect data from 403 respondents who are inclined to patronize e-stores during the pandemic. Next, the measurement model is examined using a two-step method of structural equation modeling. The findings specify that sWOM is an influential communication mode for online shopping in the pandemic. sWOM is of primary importance to information quality. Moreover, utilitarian value, social value, perceived threat, and self-efficacy toward shopping tendency are significantly motivated by sWOM. Lastly, information quality, utilitarian value, social value, and perceived threat are major predictors of shopping tendency during Covid-19. Finally, theoretical and practical implications are discussed.
Keywords: COVID-19; sWOM; Online shopping; UGT; HBT